2007
DOI: 10.1097/ico.0b013e318030d217
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin-C Concentration in Cornea and Aqueous Humor and Apoptosis in the Stroma After Topical Mitomycin-C Application

Abstract: Reducing the applied concentration or decreasing the exposure time might be a good modality for reducing the potential MMC toxicity. The applied MMC concentration had greater effects on the aqueous MMC concentration and apoptosis in the stromal cells than the exposure time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 35 publications
3
34
0
1
Order By: Relevance
“…[65][66][67] However, laboratory evidence of MMC detected in the aqueous humor has led to a concern about endothelial toxicity. [68][69][70] Clinical studies of PRK and the effect of MMC on the endothelium do not show a significant decrease in ECD or a change in cell morphology. 67,[71][72][73][74][75][76][77] Two studies report endothelial cell loss in conjunction with MMC use.…”
Section: Special Considerationsmentioning
confidence: 95%
“…[65][66][67] However, laboratory evidence of MMC detected in the aqueous humor has led to a concern about endothelial toxicity. [68][69][70] Clinical studies of PRK and the effect of MMC on the endothelium do not show a significant decrease in ECD or a change in cell morphology. 67,[71][72][73][74][75][76][77] Two studies report endothelial cell loss in conjunction with MMC use.…”
Section: Special Considerationsmentioning
confidence: 95%
“…The inhibition of keratocyte proliferation observed after photorefractive keratectomy was originally believed to be the main mechanism of MMC, since it was reported to have an antiproliferative effect on cultured human keratocytes. However, since they reported MMC cause apoptosis of cultured human keratocytes, this is now considered its main effect on corneal cells (10) . Corneal NV occurs as a sequel resulting from various causes such as infections, allergies, toxins, anoxia and immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective studies suggested that 0.02% MMC applied for 2 minutes may be as effective as higher doses but may be associated with fewer complications. [12][13][14][15][16] A variety of sponges have been advocated as vehicles for MMC, including Meroce1 and various microsurgical sponges, and it may be possible that manipulating the size or shape of the sponge can influence the effect of the MMC. 16 One study suggested that placing the sponge beneath the scleral flap rather than over intact episclera may improve the success rate without increasing complications.…”
Section: Case Reportmentioning
confidence: 99%